The Influence of Speed and Balance as Well As The Explosive Power of Leg Muscles on The Front Kick of Patbanbu Pencak Silat College Athletes During The New Normal Period - Rikardi, Riko; Welis, Wilda; Damrah, Damrah; Ihsan, Nurul (Universitas PGRI Palembang, 2024)
This study aims to determine the influence of speed and balance directly on the front kick. As well as knowing the influence of speed and balance on the front thrust through the explosive power of the leg muscles. This study used the Path Analysis design or Path Analisys. The population is male athletes of Patbanbu Pencak Silat college in Pekanbaru City with samples using purposive sampling techniques. The results of the study from the regression analysis testing of structure 1 and structure 2 showed that there was a direct influence of speed on the explosive power of leg muscles by 26.4%. There is a direct effect of balance on the explosive power of leg muscles by 23%. There is a direct influence of speed on front kick ability of 23.4%. There is a direct influence of balance on front kick ability by 1.4%. There is a direct influence of the explosive power of the leg muscles on the ability of the front kick by 72.4%. Judging from the value of α 0.05, the direct influence of speed and balance on the variable explosive power of leg muscles is all significant because the P value < 0.05. Likewise, the variables of speed, balance and explosive power against the ability of the front kick are also significant because the P value < 0.05. Furthermore, the influence of the speed variable on the ability of the front kick through explosive power was 12.6%. While the effect of balance on the ability of the front kick through explosive power is 18.5%. So it can be concluded that the better the speed, balance and explosive power of the leg muscles, the better the ability of the front kick.